Inventarisasi dan Standarisasi Resep Kue Tradisional Makassar Berbahan Dasar Tepung Beras - Nahriana Nahriana; Sukarsih A. Pangki (Seminar Nasional LP2M UNM, 2019)
This research aims to explore the traditional cakes made of rice flour. Makassarese has various traditional rice flour cakes that needs to be exposed, introduced and preserved in order to prevent it from extinction because of foreign culture invasion. This study uses descriptive and experimental design. The result of this study shows that 1) the traditional rice flour cakes grouped by processing techniques are: a) boiled: Onde-Onde, Bayao Pannyu, Kope Langi and Beppa Kawu-Kawu, b) fried: Taripang, Buah Seppang, Beppa Tori, and Cucuru Maddingki, c) steamed: Roko-Roko Unti, Putu Cangkiri, Pammoniang Talang, and Lapisi, and d) Burned / roasted: Pancake and Kaddo Boddong, 2) the panelists’ response towards the color shows that onde-onde, taripang, and putu cangkiri are the most preferred, while the rest of the cakes are categorized as good and quite good. The panelists’ response towards the aroma shows that roko-roko unti and serabi are the most preferred. The most preferred texture cakes are Lapisi, Taripang and Beppa Kawu-Kawu, 3) the process in standardized the recipes starts with making an inventory of Makassar traditional rice flour cakes, testing recipes by following the original recipes obtained from families and community leaders who know and understand the recipes, and selecting good rice flour then converted it into grams to make it easier to arrange ideal material composition